Water absorption and mechanical properties of PP/HIPS hybrid composites filled with wood flour - TAŞDEMİR, MÜNİR (WILEY, 2017)
Water absorption and mechanical performance of the injection-molded hybrid composites prepared from different ratios of two polymer blends (57 wt%), two compatibilizers (3 wt%), and two wood species (40 wt%) were investigated. The ratio of polypropylene and high-impact polystyrene (HIPS) gradually increased in the blend (from 10 to 30 wt%). Styrene-ethylene-butylene-styreneblock copolymer and maleic anhydride-grafted PP (MAPP) were used as compatibilizer (3 wt%). The shore D hardness of the PP/wood composites was improved by the incorporation of the HIPS. The HIPS/wood flour composites showed higher tensile modulus but lower tensile strength than the PP/wood composites. The water resistance of the PP/wood composites decreased with increasing HIPS content. (C) 2015 Society of Plastics Engineers
Keywords: SURFACE MODIFICATION; BLENDS; AGENT